Changing the tax structure to reduce income inequality in Colombia : a microsimulation model - Ortega Rodríguez, Nicolás Alejandro (2021)
This Document simulates a change in the structure of the Colombian tax system (changes in income pension tax thresholds and marginal earner income tax rates, as well as in social contribution rates), and measures the impact of these possible reforms on disposable income inequality. Using a microsimulation model of taxes and transfers built for Colombia, called COLMOD and based on the methodology used in EUROMOD for the European Union, the study shows that large-scale changes are needed to achieve a significant reduction in inequality in Colombia. This is because the country has a large heterogeneity in income distribution and an underground (untaxed) economy that represents 49.2% of GDP (DANE). The article concludes with a discussion of the feasibility of such major tax reforms, highlighting the link between popular support for the tax system and structure of the proposed tax. Ce document simule un changement de la structure du système fiscal colombien (modification des seuils d'imposition des pensions de retraite et des taux marginaux d'imposition des revenus des salariés, ainsi que des taux de cotisation sociale), et mesure l'impact de ces éventuelles réformes sur l'inégalité des revenus disponibles. En utilisant un modèle de microsimulation des impôts et des transferts construit pour la Colombie, appelé COLMOD et basé sur la méthodologie utilisée dans EUROMOD pour l'Union européenne, l'étude montre que des changements à grande échelle sont nécessaires pour parvenir à une réduction significative des inégalités en Colombie. En effet, le pays présente une grande hétérogénéité dans la distribution des revenus et une économie souterraine (non taxée) qui représente 49,2% du PIB (DANE). L'article se termine par une discussion sur la faisabilité de ces grandes réformes fiscales, en soulignant le lien entre le soutien populaire au système fiscal et la structure de l'impôt proposé.